Prevalence, Characteristics and Clonal Distribution of Extended-Spectrum β-Lactamase- and AmpC β-Lactamase-Producing Escherichia coli Following the Swine Production Stages, and Potential Risks to Humans - Lee, Soomin; An, Jae-Uk; Guk, Jae-Ho; Song, Hyokeun; Yi, Saehah; Kim, Woo-Hyun; Cho, Seongbeom (Frontiers in Microbiology, 2021)
The worldwide spread of extended spectrum β-lactamase (ESBL) and AmpC β-lactamase (AmpC) producing Escherichia coli (ESBL/AmpC-EC) poses serious threats to public health. Swine farms have been regarded as important reservoirs of ESBL/AmpC-EC. This study aimed to determine the prevalence, ESBL/AmpC types, and clonal distribution of ESBL/AmpC-EC from swine farms and analyze the difference according to the swine production stages. In addition, we evaluated the potential risks of swine ESBL/AmpC-EC clones to humans. Individual fecal samples (n=292) were collected from weaning, growing, finishing, and pregnant pigs in nine swine farms of South Korea between July 2017 and March 2020. In total, 161 ESBL/AmpC-EC isolates were identified (55.1%), with the highest prevalence detected in the weaning stage (86.3%). The dominant ESBL and AmpC types were CTX-M-55 (69.6%) and CMY-2 (4.3%), respectively. CTX-M found in all production stages, while CMY was only found in growing and finishing stages. In the conjugation assay, the high transferability of CTX-M gene (55.8%) was identified, while the transfer of CMY gene was not identified. The major clonal complexes (CCs) were CC101-B1 (26.8%), CC10-A (8.7%), and CC648-F (2.9%). There was similarity in clonal distribution between different swine production stages within swine farms, estimated using the k-means analysis, which suggested a clonal transmission between the different swine stages. Among swine ESBL/AmpC-EC sequence types (STs), seven STs (ST101, ST10, ST648, ST457, ST410, ST617, ST744) were common with the human ESBL/AmpC-EC which registered in National Center for Biotechnology Information database. The clonal population structure analysis based on the virulence factor presented that swine ESBL/AmpC-EC clones, especially ST101-B1, harbored a highly virulent profile. In conclusion, ESBL/AmpC-EC was distributed throughout the swine production stages, with the highest prevalence in the weaning stage. The CTX-M was present in all stages, while CMY was mostly found in growing-finishing stages. The swine ESBL/AmpC-EC was identified to harbor shared clone types with human ESBL/AmpC-EC and a virulent profile posing potential risks to humans. Considering the possibility of genetic and clonal distribution of ESBL/AmpC-EC among swine production stages, this study suggests the need for strategies considering the production system to control the prevalence of ESBL/AmpC-EC in swine farms.